Leadership studies in anchient chinese political thought - Kuppayeva B Т (Journal of Oriental Studies, 2016)
This article is about the fact that the problem of political leadership attracts the attention of thinkers for centuries. In the mystery of this phenomenon has tried to get from the earliest times. During this period, the leadership in politics was of personal character, representing the influence based on the authority of a particular individual, its merits. The relationship of the leader and his supporters were close to the relationship «teacher – student», as political activity is directly linked to the decision philosophical issues proclamation of certain moral values.